DAMPAK PENUTUPAN POS LINTAS BATAS NEGARA (PLBN) ARUK TERHADAP SOSIAL EKONOMI KELUARGA PEKERJA MIGRAN INDONESIA DI MASA PANDEMI COVID-19 - Desi Yuniarti (Cross-border, 2019)
This study aims to get a complete picture of the Sambas Regency government policy in dealing with the impact of closing the Aruk State Border Post (PLBN) as a preventive policy for the spread of Covid-19. Employment is everything related to labor at the time before, during and after the completion of the employment relationship, both in work that produces goods or work in the form of: From the aspect of employment law, it is a private law field that has a public aspect, because even though the employment relationship is made based on the freedom of the parties, there are a number of provisions that MUST be subject to government provisions in the sense of public law. The research approach used is a normative juridical approach. The results of this study indicate that the common thread of this policy is the socioeconomic family of Indonesian migrant workers. The impact of the social and economic sectors as well as the supporting and inhibiting factors for the construction of the Aruk Cross-Border Post (PLBN) in Sajingan Besar, Sambas Regency, West Kalimantan Province. The renewal of the operation of the Aruk PLBN in Sajingan Besar, which is currently a cross-country gateway, in addition to guarding the border area, of course, the Aruk PLBN can have an impact on the community in various sectors such as the social and economic sectors. Due to COVID-19 starting to become global, the critical front points prioritized are border pockets between countries. When large-scale social restrictions (PSBB) were imposed in several regions, areas and entrances such as airports, ports, and cross-border posts (PLBN) played an important role in breaking the chain of this pandemic. The PSBB is under the auspices of Law No. 6 of 2018 concerning Health Quarantine (Article 15, 2b). This law states that the central government and local governments are responsible for implementing PSBB. That is why, the security and resilience of the PLBN is in their hands.